Genital ulcers: it is not always simplex …. (January 2015) - Haidari, G; MacMahon, E; Tong, CYW; White, JA
Patients with vulval aphthae, also termed Lipschütz ulcers, often present to genitourinary medicine clinics. Typically, these ulcers present as acute, painful, vulval ulcers in young women and adolescents. The aetiology is unknown, and often these ulcers are accompanied by flu-like symptoms. Previous case reports have linked such lesions to acute viral infections such as Epstein–Barr virus, cytomegalovirus and influenza A. We report the first case of influenza B virus and adenovirus infections associated with this presentation.